Barriers to integrating ICT into the UK primary school curriculum: a case study approach - Gray, Timothy (2011)
The research question which guided this exploratory case study is, in essence, looking at causes in non-implementation of change, specifically consideration of how confidence and emotions have been factors not taken into account when considering Continued Professional Development programmes and the implementation of the ICT initiative.